Robotic nipple-sparing mastectomy for the treatment of breast cancer: Feasibility and safety study. (February 2017) - Toesca, Antonio; Peradze, Nickolas; Manconi, Andrea; Galimberti, Viviana; Intra, Mattia; Colleoni, Marco; Bonanni, Bernardo; Curigliano, Giuseppe; Rietjens, Mario; Viale, Giuseppe; Sacchini, Virgilio; Veronesi, Paolo
Abstract: Background: We previously devised and reported on an innovative surgical technique of robotic nipple-sparing mastectomy and immediate robotic breast reconstruction. Here we describe the outcome of the first 29 such consecutive procedures performed on breast cancer patients to assess feasibility, reproducibility and safety. Methods: The following morbidity factors were tested: operation time, conversion rate to open technique, length of hospitalization, registration of complications for 1 year postoperatively and their characterization as either minor, major, or multiple, depending on clinical severity and treatment required. Results: The total duration of the final robotic surgeries of our series was around 3 h, showing a very rapid learning curve. The conversion rate due to technical problems was 2 of the 29 procedures (6, 9%). No major complications, including hematoma, seroma, skin or nipple-areola injury or necrosis or infection were observed for any case. Two patients had a small degree of blistering from internal electrocautery in the breast skin flap, both of which resolved in one week without any specific therapy. No systemic complications were observed. Conclusion: The low conversion rate to open surgery, the rapid learning curve and the low rate of post-operative complications observed in this preliminary series lead us to endorse a prospective study aimed at evaluating patient satisfaction.